1992
DOI: 10.1111/j.1151-2916.1992.tb04400.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reinforcement Particle Size on the Thermal Conductivity of a Particulate‐Silicon Carbide‐Reinforced Aluminum Matrix Composite

Abstract: The thermal conductivity of a 40 vol% silicon carbide-particulate-reinforced aluminum matrix composite was determined as a function of silicon carbide mean particle size ranging from 0.7 to 28 pm. A size dependence was found consisting of a decrease in thermal conductivity with decreasing Sic particle size. This effect is in accordance with theoretical expectations for composites with an interfacial thermal barrier at the dispersion-matrix interface. At the finest particle size of the silicon carbide, the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(91 citation statements)
references
References 11 publications
8
82
1
Order By: Relevance
“…This is especially so when there are several reported instances of significant changes in thermal conductivity in two-phase composites with volume fraction of the two phases, most notably in SiC/Al [29] and diamond/ZnS composites [30,31]. Although there is no detailed model for phonon scattering in multiple phase materials, one would expect that there would be two contributions to the thermal conductivity.…”
Section: Thermal Conductivity In Multiple Phase Compositionsmentioning
confidence: 99%
“…This is especially so when there are several reported instances of significant changes in thermal conductivity in two-phase composites with volume fraction of the two phases, most notably in SiC/Al [29] and diamond/ZnS composites [30,31]. Although there is no detailed model for phonon scattering in multiple phase materials, one would expect that there would be two contributions to the thermal conductivity.…”
Section: Thermal Conductivity In Multiple Phase Compositionsmentioning
confidence: 99%
“…In an attempt to gain a theoretical understanding of the effect of remelting duration on the TC of the SiCp-Al composites, a model proposed by Hasselman and Johnson (H-J model), which has been widely used for the TC prediction of particle-reinforced composite [29], was utilized to predict the TC of the present composites. Hasselman and Johnson have shown that the TC of a composite with continuous matrix and dilute volume fraction of spherical reinforcements can be expressed as follows: In summary, the extension of the remelting duration could decrease the amount of pores in the composite microstructure and thus enhance its density.…”
Section: Thermal Conductivity Of Sicp-al Compositesmentioning
confidence: 99%
“…In an attempt to gain a theoretical understanding of the effect of remelting duration on the TC of the SiC p /Al composites, a model proposed by Hasselman and Johnson (H-J model), which has been widely used for the TC prediction of particle-reinforced composite [29], was utilized to predict the …”
Section: Thermal Conductivity Of Sic P /Al Compositesmentioning
confidence: 99%
“…If the thermal resistance has a significant impact on the thermal conductivity, the particle size is one of the essential parameters for determining it. Numerous studies on composite systems [17][18][19][20][21][22] such as Ni/glass, ZnS/diamond, SiC/Al, diamond/Al, diamond/epoxy resins, and aluminum nitride powder filled polyimide (ANI/PI) showed that their effective conductivity may decrease with increasing particle size. This is because as the particle size decreases, the interfacial surface area between particles and the matrix increases.…”
Section: Interfacial Boundary Resistancementioning
confidence: 99%